Artificial Intelligence in Retail Banking: Opportunities and Challenges - AlNeyadi, Mouza Abdulla (2023)
The research examined the opportunities and challenges related to implementing artificial intelligence (AI) in the retail banking industry in United Arab Emirates, specifically Abu Dhabi. The researcher used a qualitative research technique (a semi-structured interview) to investigate the experiences and perceptions of various senior managers and employees at First Abu Dhabi Bank, Abu Dhabi Commercial Bank, and Abu Dhabi Islamic Bank. Moreover, the researcher incorporated descriptive statistics to capture customers' behaviors toward using AI. The researcher assessed the opinions of the customers of these banks. As a result, 53 participants were incorporated into this study. The data was analyzed using thematic analysis to understand the challenges and opportunities in retail banking in Abu Dhabi. The findings highlighted the multifaceted nature of AI adoption, revealing the potential benefits, such as enhanced customer experiences and operational efficiency, as well as the challenges related to data privacy, regulatory compliance, and customer trust.